Urgensi Psikologi Belajar dalam Layanan Bimbingan dan Konseling - Syaddiyah, Halimahtun; N, Neviyarni; Nirwana, Herman (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The urgency of integrating educational psychology into guidance and counseling services is increasing in response to the growing complexity of learning challenges in modern education. This article aims to examine the role of learning psychology in enhancing the effectiveness services through a qualitative literature study approach. Data were collected from academic journals, reference books, and relevant research reports, and analyzed using content analysis techniques. The findings reveal that psychological principles such as behaviorism, cognitivism, and constructivism strengthen counseling interventions in terms of motivation, learning strategies, and student autonomy. This integration contributes to a deeper understanding of learners’ characteristics and supports more adaptive and personalized counseling approaches. The study emphasizes the importance of educational psychology training for counselors and suggests future research using action-based or experimental methods.